PENGARUH FREKUENSI IRIGASI TERHADAP PERTUMBUHAN DAN PRODUKSI LIMA GALUR PADI SAWAH - Eko Sulistyono; - Suwarno; Iskandar Lubis; Deni Suhendar (Universitas Trunojoyo Madura, 2012)
The research was conducted in February-July 2010 in the greenhouse University Farm, Cikabayan, Dramaga, Bogor. This study aims to determine the effect of irrigation frequency on growth and production of five strains of lowland rice, to determine critical point of soil water potential for drought tolerant screening. This study used a randomized block design which consists of two factors and three replications for each combination of treatments. The results of this study indicate that the frequency of irrigation effect on plant height at 8 and 12 weeks after planting (WAP), the number of tillering at 8 and 12 WAP, leaf length, ratio length / width of leaves, flowering age, number of productive tillers, panicle length, panicle number, number of grain per panicle, the percentage amount of grain fill, the weight of dry grain harvest, canopy dry weight, dry weight of milled grain, and the percentage decrease in production. Drought stress decreased production by 32.44%, 41.52% and 48.87% respectively at irrigation frequency of 8, 12, and 16 days. At optimum conditions of water availability, rice strains that produce the highest production is strain 1, 2, and 5. In drought conditions, all strains tested decreased production. Critical point of soil water potential were -35.9, -25.8 and 0.3 kPa respectively on the vegetative phase, reproductive phase, and ripening phase.